How Useful is Monetary Econometrics in Low-Income Countries? : T+L3104he Case of Money Demand and the Multipliers in Rwanda - Di Bella, Gabriel (IMF Working Papers; Working Paper ;, 2005)
This paper revisits the usefulness of econometric monetary analysis in low-income countries in a case study on Rwanda, an interesting case given its floating exchange rate and reliance on indirect monetary policy instruments on the one hand, and its somewhat typical data and institutional shortcomings on the other hand. The findings are generally encouraging for the use of econometric models for monetary analysis in low-income countries. Notwithstanding substantial qualifications, time series and structural models of the money multiplier and money demand yield results that are statistically and economically reasonable enough to usefully inform policymaking.